Unemployment insurance and deteriorating self-rated health in 23 European countries. Issue 7 (10th March 2014) - Ferrarini, Tommy; Nelson, Kenneth; Sjöberg, Ola
Abstract : Background: The global financial crisis of 2008 is likely to have repercussions on public health in Europe, not least through escalating mass unemployment, fiscal austerity measures and inadequate social protection systems. The purpose of this study is to analyse the role of unemployment insurance for deteriorating self-rated health in the working age population at the onset of the fiscal crisis in Europe. Methods: Multilevel logistic conditional change models linking institutional-level data on coverage and income replacement in unemployment insurance to individual-level panel data on self-rated health in 23 European countries at two repeated occasions, 2006 and 2009. Results: Unemployment insurance significantly reduces transitions into self-rated ill-health and, particularly, programme coverage is important in this respect. Unemployment insurance is also of relevance for the socioeconomic gradients of health at individual level, where programme coverage significantly reduces health risks attached to educational attainment. Conclusions: Unemployment insurance mitigated adverse health effects both at individual and country-level during the financial crisis. Due to the centrality of programme coverage, reforms to unemployment insurance should focus on extending the number of insured people in the labour force.